2016
DOI: 10.1093/ehjci/jew069
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic arterial measurements in complex congenital diseases before bidirectional Glenn: comparison with cardiovascular magnetic resonance imaging

Abstract: This study demonstrates modest agreement between echocardiographic and CMR measures of vessel diameter and stenosis detection. Approximately a quarter of all vessel segments could not be measured using echocardiography due to poor image quality, which was significantly lower in non-sedated patients. These findings show that echocardiography cannot substitute CMR for reliable identification of great vessel stenoses in complex patients prior to the BCPC, particularly those with Blalock-Taussig shunts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The diagnostic accuracy of echocardiographic measures of great vessels in patients before bidirectional cavopulmonary connection (BCPC) was compared with CMR by Krupickova et al 63 They showed that echocardiography cannot substitute CMR for reliable identification of great vessel stenoses in complex patients prior to the BCPC, particularly those with Blalock-Taussig shunts.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…The diagnostic accuracy of echocardiographic measures of great vessels in patients before bidirectional cavopulmonary connection (BCPC) was compared with CMR by Krupickova et al 63 They showed that echocardiography cannot substitute CMR for reliable identification of great vessel stenoses in complex patients prior to the BCPC, particularly those with Blalock-Taussig shunts.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Advanced diagnostics are required for interstage assessment of anatomy since echocardiography is insufficient for evaluation of thoracic vasculature. 1,2 Patients are the most hemodynamically fragile between the first and second stage palliation superior cavopulmonary connection (SCPC) and the risks of sedation and anesthesia required for advanced diagnostic testing is relatively high. 3 This includes adverse events from anesthesia, vascular access complications, and concerns regarding long-term effects of radiation exposure at young ages.…”
Section: Introductionmentioning
confidence: 99%